2006
DOI: 10.1111/j.1095-8649.2006.01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Within‐population heterogeneity of habitat use by lake trout Salvelinus namaycush

Abstract: To learn more about the degree of individual variation in resource use by lake trout Salvelinus namaycush, ultrasonic telemetry was used to study their habitat use in a lake without pelagic schooling fish prey. Individuals spent most of their time within the metalimnion in favourable water temperatures. They also made frequent excursions, however, into lake temperatures exceeding their optimum for physiological performance at all temporal scales considered. Their frequent use of nearshore habitats suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 44 publications
6
66
0
1
Order By: Relevance
“…However, our results support recent research findings that indicated no effect of body size on intraspecific patterns of home range/activity space (Lowry & Suthers 1998, Weller & Winter 2001, Sakaris et al 2003, Morbey et al 2006 and movement patterns (Bourke et al 1997, Egli & Babcock 2004, Ng et al 2007, Childs et al 2008, Koster & Crook 2008. Only the mean and maximum distances moved by schoolmaster snapper were marginally significant (0.1 > p > 0.05; Table 1), likely because 3 of the larger individuals moved outside the home site zones (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, our results support recent research findings that indicated no effect of body size on intraspecific patterns of home range/activity space (Lowry & Suthers 1998, Weller & Winter 2001, Sakaris et al 2003, Morbey et al 2006 and movement patterns (Bourke et al 1997, Egli & Babcock 2004, Ng et al 2007, Childs et al 2008, Koster & Crook 2008. Only the mean and maximum distances moved by schoolmaster snapper were marginally significant (0.1 > p > 0.05; Table 1), likely because 3 of the larger individuals moved outside the home site zones (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…The activity space of individual fish also differed based on spatial orientation and location. Such intrapopulation variation has been shown to be important in several freshwater fish taxa (Bourke et al 1997, Morbey et al 2006, Kobler et al 2009), and we provide one of the first extensions of this research framework to marine fishes (cf. Egli & Babcock 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed field studies have previously found that lake trout behaviorally thermoregulate seeking coldwater refuges in the summer months (33,35,36). Despite a preference for cold water, summer tracking data have shown that lake trout occasionally take short forays into the littoral zone, in the summer, which is expected to be driven by the search for prey (35). Interestingly, a classic account of lake trout natural history anecdotally notes that fishermen claim to catch lake trout from shore all year long in northern areas, whereas at the southern end of the species' range this is not the case (37).…”
Section: Resultsmentioning
confidence: 99%
“…Lake trout tend to reside in the cold pelagic zone of northern post-glacial lakes, avoiding the warm near-shore littoral habitat during the summer months. While lake trout forage on the cold-water pelagic food chain, they are still capable of making short foraging bouts into the warmer nearshore food chain 29 . Littoral coupling strength, however, depends on environmental conditions (for example, littoral habitat size) 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Lake trout prefer coldwater habitats (8-12 °C) 31,32 , and so are thermally constrained to limited foraging bouts in the warm near-shore habitat during summer months (~20 °C average summer water temperature at the southern end of their zoogeographic range) (A.1, Supplementary Discussion). In the southern end of their distribution where most data are collected, for example, lake trout are capable of short foraging bouts into the warm littoral zone 29 . As prey distributions in the near-shore zone also tend to show the highest densities at the lake edge (A.2, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%